If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -16 = x + 36 Reorder the terms: -16 + 2x = x + 36 Reorder the terms: -16 + 2x = 36 + x Solving -16 + 2x = 36 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -16 + 2x + -1x = 36 + x + -1x Combine like terms: 2x + -1x = 1x -16 + 1x = 36 + x + -1x Combine like terms: x + -1x = 0 -16 + 1x = 36 + 0 -16 + 1x = 36 Add '16' to each side of the equation. -16 + 16 + 1x = 36 + 16 Combine like terms: -16 + 16 = 0 0 + 1x = 36 + 16 1x = 36 + 16 Combine like terms: 36 + 16 = 52 1x = 52 Divide each side by '1'. x = 52 Simplifying x = 52
| 2t=-12 | | 0.1(0.1x+0.1)=-0.7 | | -(2w-3y-1)= | | 5.4q-1.5-4.9q=-0.5q-5.7 | | -6(3b+1)+(19b-3)=0 | | 6(3b+1)+(19b-3)=0 | | 2(a+4)=32 | | 4(x-7)=2x+8 | | r(r-5)=-6 | | 16(3x-7)=4(12x+6) | | 8+12t-3=6t+25-4t | | 2t+10t=24 | | 5(2+x)-3(3x+2)=-5 | | u=10v | | x+0.18=-0.14 | | 30+38-2x=787 | | (4W+6)-2W=(W-6)+10+14 | | X^3-14X+42=0 | | 12-x=16+5x | | 4.6q-2.8-5.5q=1.9q-4.8 | | y(y-5)-7(y-5)= | | -(7y+5)-(6y-7)=-6 | | 13x+7-4=12x-3 | | (1+2i)+(3+7i)-2(1-i)= | | 120=w+4 | | 45a^3d-75a^2d^2-30ad^3= | | 3a+1.50(268-a)=2084 | | 3a+1.50(216-a)=888 | | (3a+5)(2a-7)= | | -6x^2+8=0 | | x^3-8x-9= | | b^2-7b-44= |